Effects of temperature and fiber orientation on the tensile behavior of short carbon fiber reinforced PEEK composites. Issue 2 (19th October 2020) - Chang, Baoning; Gu, Junfeng; Long, Zhiqiang; Li, Zheng; Ruan, Shilun; Shen, Changyu
Abstract: Short carbon fiber reinforced poly‐ether‐ether‐ketone (SCF/PEEK) composites have attracted great attention in automobile and aerospace industries for their excellent thermal and mechanical properties. To investigate the anisotropy and temperature effects on mechanical properties of SCF/PEEK composites, tensile tests were conducted in various mold flow directions at 23, 80, 140, and 200°C. Results show that the tensile behavior of SCF/PEEK is highly influenced by temperature and fiber orientation. Both tensile strength and elastic modulus decrease with the increasing of temperature, and fracture strain increases with the increasing of temperature. Scanning electron microscopy was conducted to investigate the effects of anisotropy and temperature on fracture mechanism by scanning the tensile fracture surfaces. A shell‐core‐shell structure across the sample thickness was observed. Fibers are mainly aligned in mold flow direction in shell layers and perpendicular to the mold flow direction in core layers. The anisotropy of SCF/PEEK composites is fiber orientation dominated, and the temperature‐dependence of SCF/PEEK is matrix‐dominated. The variations of elastic modulus and tensile strength with temperature were mathematically represented. Constitutive model was established to predict the stress‐strain curves over a wide range of temperatures. Overall, the constitutive model could predict the temperature dependent stress‐strain relationships well. Abstract :